Correlation between Microstructural Characteristics and Corrosion Properties of Mg-RE Alloys in Ringer's Solution. Issue 16 (4th January 2021) - Emami, Mohammad; Bozorg, Mansoor; Binesh, Behzad; Jafari Nodooshan, Hamid Reza
Abstract : The effects of aging heat-treatment and cooling rate from annealing temperature on the microstructure and corrosion properties of a cast Mg-5Gd-2.5Nd-0.5Zn-0.5Zr alloy were studied. The as-cast structure comprised Gd/Nd-rich eutectic phases in α -Mg grain boundaries. In water-quenched and aged specimens, fine Zn/Zr-rich precipitates were developed in the matrix. Furnace cooling caused a significant increase in the volume fraction of both fine and coarse precipitates because of the large difference between the solubility of alloying elements at elevated and room temperatures. Immersion tests for up to 240 h in Ringer's solution showed a respective corrosion rate of 0.84, 0.73, 0.41, and 0.39 mm y −1 for the furnace-cooled, as-cast, water-quenched, and aged samples. The corrosion behavior was further studied by electrochemical impedance spectroscopy and polarization measurements after 1 and 24 h of immersion in the solution. An increase in the volume fraction of Gd/Nd-rich phases led to a decrease in the corrosion resistance. Large second phases acted as cathodic sites for galvanic corrosion and also locally disturbed the protectiveness of the Mg(OH)2 passive film. Rare earth elements in solid-solution were less detrimental to the corrosion resistance. Less severe corrosion resulted according to SEM observations in the aged and water-quenched samples.